Immunomodulatory Effects of Phaleria macrocarpa Leaf Extract in Normal And Cyclophosphamides Induced in Wistar Rats - Febriady, Andy; Harahap, Urip; Yuandani, Yuandani (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Abstract. Cyclophosphamide is an antineoplastic drug belonging to the alkylating agents commonly used in treating cancer. However, the use of cyclophosphamide causes a decrease in the body's immune system by reducing lymphocyte proliferation. The curent study was conducted to evaluate the immunomodulatory effect of ethyl acetate extracts of the leaf of the P. macrocarpa (EEADMD) and the ethanol extracts of the leaf of the P. macrocarpa (EEDMD) in normal and cyclophosphamide induced rats. This study used rats classified into two major groups: normal rats and rats induced by cyclophosphamide which were then given P. macrocarpa leaf extract until day 14. On day 4, the test animals were infected with 1% Staphylococcus aureus suspension in. Induced with cyclophosphamide 70 mg/kg BW was carried out on the 8th and 13th days, and then the immunomodulatory activity was tested using total leukocyte analysis, leukocyte differential, and delayed type hypersensitivity response. The results showed that EEDMD 400 mg/kg BW Â in normal rats and EEDMD 100 mg/kg BW in cyclophosphamide induced rats could increase total leukocytes and leukocyte differential with a significant difference to the negative group (p <0.05). The results of the delayed hypersensitivity response test of EEADMD and EEDMD at a dose of 100 mg/kg BW with cyclophosphamide induction and normal rats could give an increase in rat paw volume with a significant difference to the negative group (p <0.05). This study shows that EEADMD and EEDMD have an immunomodulatory effect on increasing total and differential leukocytes and leukocyte differential and delayed type hypersensitivity response.